The lattice structure design and strength analysis for a 3D printed material - Xue, Mengmeng (Nanyang Technological University, 2024)
Multi-Metal Additive Manufacturing (MAM) technology boasts advantages such as flexible material combinations and complete machine manufacturing, thereby offering more opportunities for lightweighting, noise reduction, and thermal/structural stability optimization in high-performance aerospace components. However, owing to the limited reaction and mutual solubility between two alloying elements, as well as thermal mismatch at the interface, parts fabricated through multi-material additive manufacturing tend to be susceptible to stress concentration and thermal mismatch.